A rare tumor and an ethical dilemma in a family with a germline TP53 mutation - Procházková, Kamila; Foretová, Lenka; Sedláček, Zdeněk (Cancer genetics and cytogenetics, 2008)
We describe a family with a history of cancer suggestive of the Li-Fraumeni syndrome (LFS). A 27-year-old woman suffered at 17 years of age from phyllodes breast tumor and was shown to carry a germline mutation in the TP53 gene. Two years after testing, she became pregnant and was offered prenatal diagnosis by her gynecologist. The patient expressed her commitment to deliver the baby regardless of its mutation status, but with a strong interest in having the child tested soon after the birth. When she was informed that testing of children is usually postponed until after they reach 18 years of age, she consulted several geneticists, who repeatedly discouraged her from the intent to test the newborn. In the end, the patient decided for prenatal genetic testing only to learn the mutation status of the child. This scenario being unacceptable, she was offered early postnatal testing of the child, and this analysis showed that the newborn boy carried the mutation. Based on this finding, the family was enrolled into a preventive screening program for childhood cancer. The case illustrates ethical problems associated with early predisposition testing in LFS, and the lack of consensus on this issue in the literature.
Keywords: Liův-Fraumeniho syndrom; zárodečné mutace; Male; Pregnancy Complications, Neoplastic; Pedigree; Genetic Predisposition to Disease; rodokmen; Li-Fraumeni Syndrome; Phyllodes Tumor; Adolescent; Pregnancy; těhotenství; Adult; dospělí; mužské pohlaví; cystosarcoma phyllodes; Genes, p53; mladiství; novorozenec; geny p53; Germ-Line Mutation; lidé; ženské pohlaví; Humans; Genetic Counseling; Infant, Newborn; Financing, Organized; Female; financování organizované; genetická predispozice k nemoci; nádorové komplikace v těhotenství; genetické poradenství